The Selenocysteine-Specific Elongation Factor Contains Unique Sequences That Are Required for Both Nuclear Export and Selenocysteine Incorporation - Dubey, Aditi; Copeland, Paul R. (PLOS ONE, 2016)
Selenocysteine (Sec) is a critical residue in at least 25 human proteins that are essential for antioxidant defense and redox signaling in cells. Sec is inserted into proteins cotranslationally by the recoding of an in-frame UGA termination codon to a Sec codon. In eukaryotes, this recoding event requires several specialized factors, including a dedicated, Sec-specific elongation factor called eEFSec, which binds Sec-tRNASec with high specificity and delivers it to the ribosome for selenoprotein production. Unlike most translation factors, including the canonical elongation factor eEF1A, eEFSec readily localizes to the nucleus of mammalian cells and shuttles between the cytoplasmic and nuclear compartments. The functional significance of eEFSec’s nuclear localization has remained unclear. In this study, we have examined the subcellular localization of eEFSec in the context of altered Sec incorporation to demonstrate that reduced selenoprotein production does not correlate with changes in the nuclear localization of eEFSec. In addition, we identify several novel sequences of the protein that are essential for localization as well as Sec insertion activity, and show that eEFSec utilizes CRM1-mediated nuclear export pathway. Our findings argue for two distinct pools of eEFSec in the cell, where the cytoplasmic pool participates in Sec incorporation and the nuclear pool may be involved in an as yet unknown function.